Thermal Deformation Analysis of a Star Camera to Ensure Its High Attitude Measurement Accuracy in Orbit - Fan Jiang; Lei Wang; Huaxia Deng; Lei Zhu; Dezhu Kong; Hongyu Guan; Jinguo Liu; Zhongsu Wang (Remote Sensing)
With the continuous advancement of high-resolution satellite technology, the impact of thermal deformation on the performance of star cameras is becoming more significant, particularly in relation to installation conditions and orbital environments. To address this challenge, an in-depth investigation of the thermal design of a star camera is conducted in this study. The thermal deformation of this camera is evaluated systematically through simulation analysis, thermal balance tests, and on-orbit temperature measurements. In addition, a simulation analysis is used to identify and quantitatively evaluate the thermal deformation error sources that affect the spatial attitude measurement accuracy of the star camera. The results indicate that thermal deformations of the optical system, the mounting surface of the star camera, and the support significantly impact on-orbit measurement accuracy. Ultimately, the limit error attributable to on-orbit thermal deformation is determined to be 0.62″. In the thermal balance experiments, the maximum absolute difference between the test results and the thermal simulation analysis results is under 1.8 °C. Additionally, analysis of the orbital temperature data reveals that the maximum absolute difference between the orbital results and the thermal simulation results is 1.18 °C, while the attitude accuracy of the star sensor is better than 0.54″. These findings validate the effectiveness of the thermal design and the accuracy of the thermal simulation analysis. The analysis of error sources presented in this paper offers crucial insights for effectively controlling the thermal deformation errors of star cameras and lays the groundwork for optimizing overall thermal design.